2017
DOI: 10.1111/tpj.13393
|View full text |Cite
|
Sign up to set email alerts
|

Choline transporter‐like1 (CHER1) is crucial for plasmodesmata maturation in Arabidopsis thaliana

Abstract: 195 Identifi cation of a residue responsible for UDP-sugar donor selectivity of a dihydroxybenzoic acid glycosyltransferase from Arabidopsis natural accessions. H.-Y. Chen and X. Li 204 PYK10 myrosinase reveals a functional coordination between endoplasmic reticulum bodies and glucosinolates in Arabidopsis thaliana. R.T. Nakano, M. Pis´lewskaPis´lewska-Bednarek, K. Yamada, P.P. Edger, M. Miyahara, M. Kondo, C. Böttcher, M. Mori, M. Nishimura, P. Schulze-Lefert, I. Hara-Nishimura and P. Bednarek 221 Identifi ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…Furthermore, recent work has demonstrated that impairing choline transport, by CHER1 choline transporter inactivation, has an impact on the development of the root vasculature and plasmodesmata in particular (Dettmer et al, 2014;Kraner et al, 2017). In light of the absence of strong architectural alterations and lipid modifications caused by the greatly diminished PCho concentration in our plant lines, the CHER1 mutant phenotype is more likely linked to choline or PtdCho imbalance rather than to lower PCho content (Kraner et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, recent work has demonstrated that impairing choline transport, by CHER1 choline transporter inactivation, has an impact on the development of the root vasculature and plasmodesmata in particular (Dettmer et al, 2014;Kraner et al, 2017). In light of the absence of strong architectural alterations and lipid modifications caused by the greatly diminished PCho concentration in our plant lines, the CHER1 mutant phenotype is more likely linked to choline or PtdCho imbalance rather than to lower PCho content (Kraner et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
“…In light of the absence of strong architectural alterations and lipid modifications caused by the greatly diminished PCho concentration in our plant lines, the CHER1 mutant phenotype is more likely linked to choline or PtdCho imbalance rather than to lower PCho content (Kraner et al, 2017).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…and Cho (Jost et al, 2009). NMT1 expression is known to be sensitive to feedback inhibition leaves (Dettmer et al, 2014;Kraner et al, 2017). Choline has also long been known to be 582 present in xylem sap (Maizel et al, 1956;Martin et al, 1983).…”
mentioning
confidence: 99%
“…The molecular mechanisms and role of such dynamic modification of PD frequency are unknown. Recently, however, it has been reported that a choline transporter is involved in the insertion of secondary PD during Arabidopsis development [77]. Mutants in CHOLINE TRANSPORTER-LIKE 1 ( CHER1 ), which encodes a choline transporter, have altered the localization of a plant virus movement protein at PD.…”
Section: Regulatory Mechanisms Of Pd Movementmentioning
confidence: 99%